COMPARATIVE STUDY ON SURFACE CONTAMINATION DURING DENTAL TREATMENTS GENERATING AEROSOLS - Balcoș Carina; Livia Bobu; Irina Bamboi; Anca Rapis; Ramona Feier; Dana Baciu; Irina Grădinaru; Georgiana Macovei; Laura Checheriță; Loredana Hurjui; Vlad Danilă; Adina Armencia; et al. (Romanian Journal of Oral Rehabilitation, 2023)
Most dental procedures that use handpieces, turbines, US scalers, airflow, and air abrasion tend to produce aerosols in which the patient’s oral fluids are also entrained, with consequences on the health of the medical staff and other patients. Oral fluids are highly contaminated with microorganisms. The aim of the study was to assess the degree of surface contamination in relation to certain variables of the aerosol-generating dental maneuvers. Material and methods: 2 operators performed 5 simulations of 10 min each for treatments with US scaler, turbine, and contra-angle with spray cooling system. The evaluation of the contaminated surfaces was carried out by measuring the colored surface, in cm, on the paper sheet that was placed on the mannequin, starting from the oral cavity of the mannequin. The measurements were made in all 4 directions (right, left, superior, inferior) to see which part of the operative field is more prone to contamination. Statistical analysis of the collected data was carried out using the SPSS 26.0. Result: Dental turbine operations will produce a significant number of aerosols, the most of them in the form of droplets, spanning regions up to 60 cm. US scaling produced less aerosols than the other activities, with the least contaminated surface. Statistics have proven that the observed differences are different (p=0.000). Conclusions: The surfaces were contaminated by all three aerosol-producing dental procedures at various and equivalent distances. The turbine produced a greater amount of aerosols, especially in the form of droplets, that exceeded the maximum contamination zone with an area of 1m